Predicting radiographic hip osteoarthritis from range of movement. - Birrell, F; Croft, P; Cooper, C; Hosie, G; Macfarlane, G; Silman, A (2001)
OBJECTIVES: The primary objective was to test the hypothesis that new attenders in primary care with hip pain and radiographic osteoarthritis (OA) have a decreased range of movement compared with those without OA. The secondary objective was to define the planes of movement and thresholds that were the most discriminatory for OA. METHODS: Men and women aged 40 yr and over presenting with a new episode of hip pain were recruited from 36 general practices across the UK. A standardized radiographic and clinical examination was performed. The discriminating ability of the range of movement for each plane to identify those with radiographic OA was assessed using receiver operating characteristic curves. RESULTS: New hip pain attenders with radiographic OA had restricted movement at the hip compared with those without radiographic change. Restriction in internal rotation was the most predictive and flexion the least predictive of radiographic OA. At this cut-off, restriction in any single plane had a sensitivity of 86% for moderate and 100% for severe OA (specificity was 54 and 42% respectively). Restriction in all three planes had greater discrimination (sensitivity was 33% for mild to moderate OA and 54% for severe OA; specificity was 93 and 88% respectively). CONCLUSIONS: Restriction in range of movement was predictive of the presence of OA in these new presenters to primary care with hip pain, and the results of this examination could be used to inform decisions regarding radiography.